Perilaku Destruktif Dalam Politik Standar Ganda Amerika Serikat Terhadap Demokratisasi Mesir dan Suriah - Hidayat, Yogi Fery (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
Hypocrisy is a trait that is very hated in Islam and is a disgraceful trait for its adherents. Hypocrisy is a trait possessed by the enemies of Islam who want to destroy the glory of Islam from within, even trying to destroy Islamic countries, especially those in the Middle East, where Islam first appeared and spread widely among Arabs. This paper aims to find out the practice of hypocritical behavior that occurs at the country level by using a qualitative method that focuses on a literature approach, That is by collecting data obtained from various references in the form of articles, journals, books and research related to material objects and formal objects which are then analyzed using the conspiracy theory of Robert O Zelency (1987). The result of this research is the double standard political success played by the United States who wants to control the oil fields in Egypt and Syria under the guise of calling for democratization in the government system. America acts as a friend to Egypt in the process of transitioning from authoritarian power to democracy and has been very active in guarding the decline of Hosni Mubarak from his leadership, while in Syria, America has supported opposition groups to overthrow a legitimate government that is considered to be running the government in a dictatorial way. America also provided assistance to opposition groups in the form of weapons to expedite the process of overthrowing Bashar Al-Assad from power. America's double-standard politics towards Egypt and Syria is a project undertaken to realize a larger agenda in the geopolitical national political arena.